2018
DOI: 10.28978/nesciences.379319
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between total length and otolith size of bluefish Pomatomus saltatrix (Linnaeus, 1766) in the Marmara Sea of Turkey

Abstract: In the present study, bluefish, Pomatomus saltatrix, was monthly collected from commercial fishing boats operating in the Marmara Sea between January and December 2014. The relationship between total length and otolith size of 346 bluefish samples were examined. Total lengths of females, males and unidentified samples were ranged from between 13.2-37.0, 12.3-34.8 and 13.0-31.6 cm, respectively. Otolith lengths were between 3.82-12.60 mm and otolith width were between 1.59-4.34 mm for all samples. It was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Several studies on the bluefish focused on age and growth (Krug, Haimovici, 1989;Robillard et al, 2009), reproduction (Haimovici, Krug, 1992;Robillard et al, 2008), diet (Haimovici, Krug, 1992) and fisheries (Haimovici, Krug, 1996;Lucena, O'Brien, 2005). Nevertheless, studies on the morphometric relationships of bluefish otoliths are few and geographically limited in the literature (Hare, Cowen, 1995;Ceyhan, Akyol, 2006;Zengin et al, 2017;Bal et al, 2018). The aim of this paper was to provide information on the length-weight relationships (LWR) and condition factor (k) of bluefish, and the relationships between otolith dimensions and fish size, testing the hypothesis that such relations may provide useful predictive equations for estimating fish length and weight.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the bluefish focused on age and growth (Krug, Haimovici, 1989;Robillard et al, 2009), reproduction (Haimovici, Krug, 1992;Robillard et al, 2008), diet (Haimovici, Krug, 1992) and fisheries (Haimovici, Krug, 1996;Lucena, O'Brien, 2005). Nevertheless, studies on the morphometric relationships of bluefish otoliths are few and geographically limited in the literature (Hare, Cowen, 1995;Ceyhan, Akyol, 2006;Zengin et al, 2017;Bal et al, 2018). The aim of this paper was to provide information on the length-weight relationships (LWR) and condition factor (k) of bluefish, and the relationships between otolith dimensions and fish size, testing the hypothesis that such relations may provide useful predictive equations for estimating fish length and weight.…”
Section: Introductionmentioning
confidence: 99%
“…Zengin et al (2017) investigated the relationships between otolith dimensions (OL, OB and OW) and total length of bluefish and found a strong relationship between TL and OW. However, Bal et al (2018a) found a strong relationship between OL and TL. These differences can be arrise from environmental differences between Marmara and Blacksea regions.…”
Section: Discussionmentioning
confidence: 80%
“…These differences can be arrise from environmental differences between Marmara and Blacksea regions. And also Bal et al (2018a) have not examined otolith weight. The otolith shapes have been evaluated based on morphometric measurements (Short et al 2006) and the mathematical computation of shape indices (Russ, 1990;Tuset et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations